Determinants of Patient Satisfaction with Public Safety Center (PSC) 119 Prehospital Emergency Services in Non-Communicable Disease: Cases in Malang, Indonesia - Anggun Setyarini; Susi Milwati; Eko Sari Wahyuni (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Patient satisfaction is an important indicator of quality in prehospital emergency care. Globally, response time, communication, and clinical characteristics influence patient perceptions of emergency services. However, limited evidence exists regarding determinants of satisfaction with Public Safety Center (PSC) 119 services in Indonesia, particularly among non-communicable disease (NCD) cases. This study aimed to analyze factors associated with patient satisfaction toward Public Safety Center (PSC) 119 prehospital emergency services in Malang, Indonesia. A quantitative cross-sectional study was conducted involving 62 respondents who received PSC 119 services between 2024–2025. The dependent variable was overall patient satisfaction, measured using the Prehospital Emergency Care Patient Satisfaction Scale (PECPSS-20). Independent variables included sociodemographic factors (age, sex, education, income), clinical conditions (hypertension, heart disease, NCD category), and operational factor (ambulance response time). Data were collected through structured online questionnaires and analyzed using descriptive statistics, Chi-square tests, and Pearson correlation. Most respondents were within productive age (94%) and experienced NCD-related emergencies (72.6%). Overall satisfaction was high (80.6% very satisfied). Significant associations were found between satisfaction and hypertension (p=0.001), heart disease (p=0.025), education level (p=0.012), income level (p=0.008), and ambulance response time (p=0.001). Response time showed the strongest negative correlation (r = –0.397), indicating that longer delays significantly reduced satisfaction.Patient satisfaction with PSC 119 services is strongly influenced by clinical comorbidities, socioeconomic characteristics, and particularly response time. Improving dispatch efficiency and reducing ambulance response delays are essential strategies to enhance prehospital emergency service quality.